Methodological Issues of Providing Training in Prevention of Behavioural and Developmental Disorders within Master’s Programme in School Psychology - Bogdanovich N. V.; Delibalt V.V.,; Chernushevich V.A. , (Психологическая наука и образование (2007. Online), 2016)
The article explores features of providing training in the approbated module “Prevention of Behavioural and Developmental Disorders” within the master’s programme in School Psychology. The programme was developed in accordance with the professional standard for educational psychologists. The article outlines the aims of the module and its place in the context of the programme in general and reveals the main ways of developing competencies specified in the educational standard but selected with respect to professional activities defined by the professional standard. The article also suggests some methodological principles of designing an educational module in practice-oriented training, among which the basic one is reflective activity-based networking. An activity-based content of the module is proposed basing on the psychological definition of prevention as one of the core activities in a psychologist’s work. Finally, the article describes educational outcomes in graduate students upon successful completion of the training, and reflects upon certain problems revealed during the approbation of the module.